Study of Medicinal Plants Used in Respiratory Disease According to Siddha Pharmacodynamics - Prasad, V.M.; Sathiyaseelan, V. (Institute of Indigenous Medicine University of Colombo, Rajagiriya Sri Lanka, 2016)
Siddha medicine is an ancient medicine, in which the treatment is given with raw material of medicinal plants. The chemical constituents are not separated and taken separately for treatment and therefore it is based on raw materials' pharmacodynamics and that indicates the action of drugs and it shows the therapeutic effect. Accordingly taken to identify the prepared medicines for respiratory disorders pharmacodynamics of the ingredients. For this study nine Siddha text books are taken and 109 prepared medicines are identified, in which 110 plants were used. There are 24 hair oils and 25 tablets, other types of prepared medicines are comparatively less. Among 110 plants in medicine preparation, 34 uses root, 18 uses seeds, 12 uses leaves, 10 are rhizomes other parts used are comparatively less. In Suvai 50 are bitter, 35 pungent, 18 astringent and 20 sweet. In which some of the plant parts has two tastes. In Veeriyam 77 are hot in potency and 33 are cold in potency. On seeing Vipakam 86 shows pungent and 24 shows sweet. According to Siddha fundamental, respiratory disorders are due to increases of Kapha. Kapha is Guru, cold in character which has Pruthvi and Appupanchapootha, so hot in character should be given for treatment, accordingly literature review says, in prepared medicines, most of the ingredients are hot in potency and has pungent Vipaka which has Vayu and the Vayupanchapootham and Laghu in character. This can neutralize kapha which is the expected findings.
Keywords: Pharmacodynamics; Panchapootham; Vayu